Immunoexpression of cyclooxygenase-1 and -2 in ulcerative colitis - Paiotti,A.P.R. (2007)
Ulcerative colitis (UC) is a disease of the colon and rectum characterized by a nonspecific chronic inflammation mediated by the concerted response of cellular and humoral events. Prostaglandins are synthesized by cyclooxygenase (COX)-1 and -2 and exhibit both pro- and anti-inflammatory activity. To evaluate COX-1 and COX-2 immunoexpression in 42 cases of UC and to correlate it with clinicopathological parameters, COX-1 and COX-2 expression was investigated by the immunohistochemistry method. Only patients with all pertinent clinical and evolutive data as well as with adequate biopsy material were included in the study. Fifteen samples of colorectal adenocarcinoma and 14 of large bowel with no histological changes were used for positive and negative controls, respectively. UC patients showed COX-1 immunoreactivity in epithelial cells in 29% of the cases and in inflammatory cells in 43%. COX-2 positivity in epithelial and inflammatory cells was found in 69% of the samples. The comparison between UC and the control groups revealed that the UC group had significantly more positive cases for COX-1 and COX-2 in inflammatory cells. Immunohistochemistry allowed the identification of COX-1 and COX-2 expression in epithelial and inflammatory cells in UC biopsies. No significant difference between COX-1 and COX-2 immunoreactivity in epithelial and inflammatory cells was observed regarding the clinicopathological parameters. COX-2 presented low expression in normal colon and high expression in colorectal adenocarcinoma. COX-2 might play a role in the pathophysiologic processes of inflammatory bowel disease and the development of neoplasia. Treatment with selective COX-2 inhibitors might be an additional option for therapy.